ATIM-32. PREDICTORS OF IMPROVED SURVIVAL FOLLOWING ONCOLYTIC VIRUS TREATMENT IN PATIENTS WITH RECURRENT GLIOBLASTOMA: GENE EXPRESSION ANALYSIS FROM THE PHASE IB G207 CLINICAL TRIAL. (11th November 2019) - Cassady, Kevin; Miller, Katherine; Prasad, Nripesh; Maric, Dragan; Bernstock, Josh; Roth, Justin; Barker, Naomi; Coleman, Jennifer; Schieffer, Kathleen; Leraas, Kristen; Miller, Anthony; Leavenworth, Jianmei; et al.
Abstract: Our Phase I trials of experimental virotherapy for recurrent glioblastoma (GBM) have shown that inoculation with a conditionally replication-competent early generation oncolytic herpes simplex virus (oHSV), G207, is safe. However, while 17 of 37 subjects experienced objective clinical responses, the highly attenuated oHSV did not uniformly improve survival. We sought to identify predictors that would identify mechanisms contributing to survival and improve future trial design, by studying accrued samples. We analyzed pre-treatment biopsy and post-G207-treatment tumor samples (collected D2-5 post injection) banked from the patients enrolled in the phase IB G207 trial. The key findings from these patients suggest that productive G207 infection and G207-induced changes in gene expression were predictive of oHSV therapeutic success. RNAseq-based transcriptome analysis of these samples revealed that both the intrinsic IFN mediated antiviral response and adaptive immune functional response in patients correlated significantly with improved survival following G207 inoculation. Further, GBM tissue stained using multiplex fluorescent immunohistochemistry supported differences in the tumor microenvironments that were identified from RNAseq data analysis. Our data indicate that both viral gene expression and the resulting intrinsic anti-viral and recruited adaptive response were critical for survival after G207 inoculation and predict survival with this early generation oHSV in patients with recurrent malignant glioma.